PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PERENCANAAN ANGGARAN, DAN POLITIK PENGANGGARAN DENGAN TRANSPARANSI PUBLIK SEBAGAI VARIABEL MODERATING TERHADAP SINKRONISASI DOKUMEN APBD DENGAN DOKUMEN KUA-PPAS PADA PEMERINTAH KOTA PEKANBARU - Habeahan, Hendita; Ratnawati, Vince; Darlis, Edfan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The Purpose of this research is to test influence the capacity of human resources, budget planning and budgeting politics on the synchronization between APBD document and KUA-PPAS document and to test the role of public transparency in moderate the relationship between the capacity of human resources, budget planning, budgeting politics with the synchronization between APBD document and KUA-PPAS document. Sample in this research are employee of SKPD. The sampling technique using purposive sampling method and there are 96 respondents. The data of this research using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach and moderated regression analysis. Result of research show that Capacity of Human Resources, Budget Planning, Political Budgeting have effect on the synchronization between APBD document and KUA-PASS document. Result of the interaction test showed that public transparency could not moderate the relationship between the capacity of human resources, budget planning and budgeting politics and the synchronization between APBD document and KUA-PASS document.Keywords: Synchronization, Human Resource Capacity, Budget Planning, Budgeting Politics, and Public Transparency